ANTIBACTERIAL ACTIVITY OF XANTHONE FROM ETHYL ACETATE EXTRACT OF THE STEAM BARK OF Garcinia picrorrhiza Miq - Muharni Muharni; Elfita Elfita; Emil Pertiwi (UNIVERSITAS SEBELAS MARET (UNS), 2017)
A compound was isolated from the ethyl acetate extract of stem bark Garcinia picrorrhiza. The extraction was conducted by maseration. Separation and purification were done by chromatography method. The structure of compound was established using UV, IR, and 1H NMR spectroscopy. The antibacteria activity of the isolated compound was tested by paper disk difusion method and minimum inhibitory concentration (MIC) value was determined by using well difusion method examined against bacteria Escherechia coli, Salmonella typhi, Bacillus subtilis and Staphyloccocus aureus. The isolated compound was a yellow solids (43.8 mg) with melting point 171 – 172 oC. Based on spectroscopy data compared with data from the literature, the isolated compound is a known compound of oxygenated xanthone group with structure 1,4,5-trihydroxy-2-(3methylbut-2-enyl)xanthone. The compound exhibited an antibacterial activity against Bacillus subtilis only with MIC of 62.5 µg/mL.